Study of isolation effectiveness of nuclear reactor building with three-dimensional seismic base isolation. Issue 4 (6th September 2021) - Zhu, Xiuyun; Pan, Rong; Li, Jianbo; Lin, Gao
Abstract : Purpose: In recent years, three-dimensional (3D) seismic base isolation system has been studied extensively. This paper aims to propose a new 3D combined isolation bearing (3D-CIB) to mitigate the seismic response in both the horizontal and vertical directions. Design/methodology/approach: The new 3D-CIB composed of laminated rubber bearing coupled with combined disk spring bearing (CDSB) was proposed. Comprehensive analysis of constitution and theoretical derivation for 3D-CIB were presented. The advantage of CDSB is that the constitution can be flexibly adjusted according to the requirements of the bearing capacity and vertical stiffness. Hence, four different combinations of CDSB were designed for the 3D-CIB and employed to isolate nuclear reactor building. A comparative study of the seismic response in terms of seismic action, acceleration floor response spectra (FRS), peak acceleration and relative displacement response was carried out. Findings: 3D-CIB can effectively reduce seismic action, FRS and peak acceleration response of the superstructure in both the horizontal and vertical directions. Overall, the horizontal isolation effectiveness of 3D-CIB was slightly influenced by vertical stiffness. The decrease in the vertical stiffness of the 3D-CIB can reduce the vertical FRS and shift the peak values to a lower frequency. The vertical peak acceleration decreased with a decrease in the vertical stiffness. The superstructure exhibited a rocking effect during the earthquake, and the decrease in the vertical stiffness may increase the rocking of the superstructure. Originality/value: Although the advantage of 3D-CIB is that the vertical stiffness can be flexibly adjusted by different constitutions, the vertical stiffness should be designed by properly accounting for the balance between the isolation effectiveness and displacement response. This study of isolation effectiveness can provide the technical basis for the application of 3D-CIB into real engineering of nuclear power plants.